1982
DOI: 10.2337/diab.31.8.738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diabetes on the Glycosaminoglycan Component of the Human Glomerular Basement Membrane

Abstract: SUMMARYThe glycosaminoglycan (heparan sulfate) component of glomerular basement membranes from human kidneys of diabetic and nondiabetic subjects has been quantitated after isolation from protease digests of the membranes on OEAE-cellulose microcolumns. A significant decrease (P < 0.005) in the glycosaminoglycan content of diabetic membranes was observed. Heparan sulfate was identified as the predominant glycosaminoglycan in both diabetic and control subjects and the extent of its sulfation appeared to be simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(46 citation statements)
references
References 9 publications
3
40
1
2
Order By: Relevance
“…The content of uronic acid and amino sugar-building blocks of GAG also decreased during diabetes resulting in decreased content of GAG. These results correlated with the studies using kidneys obtained at autopsy to measure GAG content of GBM in patients with diabetic nephropathy, which contained reduced amount of GAG than kidneys of non-diabetic controls (Parthasarathy and Spiro, 1982). Decreased synthesis of glomerular proteoglycans and basement membrane heparan sulfate proteoglycans (HSPG) during diabetes has been reported by many workers in mice and rats (Cohen and Surma, 1981;Kanwar et al, 1983;Rohrbach et al, 1983).…”
Section: Discussionsupporting
confidence: 76%
“…The content of uronic acid and amino sugar-building blocks of GAG also decreased during diabetes resulting in decreased content of GAG. These results correlated with the studies using kidneys obtained at autopsy to measure GAG content of GBM in patients with diabetic nephropathy, which contained reduced amount of GAG than kidneys of non-diabetic controls (Parthasarathy and Spiro, 1982). Decreased synthesis of glomerular proteoglycans and basement membrane heparan sulfate proteoglycans (HSPG) during diabetes has been reported by many workers in mice and rats (Cohen and Surma, 1981;Kanwar et al, 1983;Rohrbach et al, 1983).…”
Section: Discussionsupporting
confidence: 76%
“…However, the degree of sulphating of the GAGs is not affected [3]. Thus, the decrease in total sulphated GAG excretion observed in the present study probably reflects a real decrease in amount of GAG.…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, there is a decrease or redistribution in negatively charged groups of GAGs [1, 2, 3, 4, 5, 28]in the GBM. Hypothetically, as mentioned above, this may lead to albuminuria [7, 13]and increased excretion of IgG4 [8, 9, 10, 11, 12, 13, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies on human diabetic kidney tissues, the structural or compositional changes found in GBM and podocytes showed increases in the amount of type IV collagen, laminin, and fibronectin, with a simultaneous reduction in the anionic components including HSPG [9]. A relative reduction in heparan sulfate (HS) and HSPG was also observed in the GBM of diabetic patients [10,11,12]. Some authors have noted a decreased staining for HS side chains in the GBM in human diabetic kidneys, with no change in the GBM staining for the core protein of HSPG [4,13].…”
Section: Discussionmentioning
confidence: 93%